Antiaging Treatment of the Facial Skin by Fat Graft and Adipose-Derived Stem Cells. Issue 4 (April 2015) - Charles-de-Sá, Luiz; Gontijo-de-Amorim, Natale Ferreira; Maeda Takiya, Christina; Borojevic, Radovan; Benati, Donatella; Bernardi, Paolo; Sbarbati, Andrea; Rigotti, Gino
Abstract : Background: The regenerative property of fat grafting has been described. However, it is not clear whether the clinical results are attributable to the stem cells or are linked to other components of the adipose tissue. This work is aimed at analysis of the histologic and ultrastructural changes of aged facial skin after injection of fat graft in addition to its stromal vascular fraction, obtained by centrifugation, and to compare the results with those obtained by the injection of expanded adipose-derived mesenchymal stem cells. Methods: This study was performed in six consecutive patients who were candidates for face lift and whose ages ranged between 45 and 65 years. The patients underwent sampling of fat by liposuction from the abdominal region. The injection of fat and its stromal vascular fraction or expanded mesenchymal stem cells was performed in the preauricular areas. Fragments of skin were removed before and 3 months after each treatment and analyzed by optical and electron microscopy. Results: After treatment with the autologous lipidic component and stromal vascular fraction, the skin showed a decrease in elastic fiber network (elastosis) and the appearance of new oxytalan elastic fibers in papillary dermis. The ultrastructural examination showed a modified tridimensional architecture of the reticular dermis and the presence of a richer microvascular bed. Similar results following treatment with expanded mesenchymal stem cells were observed. Conclusion: This study demonstrates that treatment with either fat and stromal vascular fraction or expanded mesenchymal stem cells modifies the pattern of the dermis, representing a skin rejuvenation effect. Abstract : Video Discussion by Michael T. Longaker, M.D., M.B.A., is available online for this article.